Comparative Study of the Efficacy of Herbal Desensitizing Toothpaste Versus Herbal Desensitizing Mouthwash on Extracted Teeth: A Scanning Electron Microscopy Study - Apon, Adiya; Kamble, Praneeta; Prasad, Upendra (Journal of interdisciplinary dentistry, 2023)
ABSTRACT Context: Dentinal hypersensitivity is an exaggerated response to nonnoxious sensory stimuli which is viewed by individuals as an important health problem. Recently, a growing interest in herbal-based products is found to be beneficial as the conventionally based formulated product. Aims: The aim of the study was to evaluate and compare the dentinal tubule occlusion ability of herbal desensitizing toothpaste and mouthwash on extracted teeth using scanning electron microscopy (SEM) analysis. Settings and Design: This was a nonclinical, prospective study. Subjects and Methods: This study was done on 45 dentinal samples obtained from human-extracted teeth. Forty-five dentin samples were prepared, sectioned mesiodistally, etched with 6% citric acid for 2 min, washed with distilled water, and divided into: Group 1: specimens were placed in distilled water (control group) for 14 days, Group 2: specimens were brushed 2 min twice daily with HiOra-K™ toothpaste for 14 days, and Group 3: specimens were rinsed 2 min twice daily with HiOra-K™ mouthwash for 14 days. At the end of 3, 7, and 14 days, specimens were subjected to SEM analysis to detect tubular occlusion. Statistical Analysis Used: Chi-square analysis and analysis of variance were used for the significance study parameters on categorical scale and between groups (intergroup analysis) on metric parameters. Results: Toothpaste yielded better results of complete occlusion of dentinal tubules when compared with mouthwash at the end of 3, 7, and 14 days. Conclusions: Herbal desensitizing toothpaste and mouthwash occluded the dentinal tubules and are found to be effective in the management of dentinal hypersensitivity. CLINICAL RELEVANCE TO INTERDISCIPLINARY DENTISTRY Dentin hypersensitivity is a persistent clinical problem that poses significant challenge for clinicians and the patients.This study has evaluated a treatment modality for dentinal hypersensitivity using Herbal products. With the resolution of dentinal hypersensitivity it will be beneficial to the society and improve the patient's quality of life.